2020
DOI: 10.1029/2019jd031833
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Special Collection: “Bridging Weather and Climate: Subseasonal‐to‐Seasonal (S2S) Prediction”

Abstract: This article acts as an introduction to the JGR‐Atmospheres Special Section titled “Bridging Weather and Climate: Subseasonal‐to‐Seasonal (S2S) Prediction”. It outlines the major findings of the articles published in the Special Section as well as discusses organized national and international efforts to advance subseasonal‐to‐seasonal prediction research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…There has been continued development and production of climate forecasts from national and international agencies at ever higher resolution and with incremental improvements in skill (Kirtman et al., 2013; Wanders et al., 2019). Of note is the push for extended skill at sub‐seasonal time scales (beyond 2 weeks but less than seasonal) (Lang et al., 2020) that has important implications for a range of applications, including disaster risk reduction and for different economic sectors (Morss et al., 2008). Criteria for choosing a set of seasonal climate models are based on their resolution (space and time), availability of hindcasts (historic forecasts) to evaluate their skill, the skill of the models for the particular application, and availability of forecasts operationally.…”
Section: Introductionmentioning
confidence: 99%
“…There has been continued development and production of climate forecasts from national and international agencies at ever higher resolution and with incremental improvements in skill (Kirtman et al., 2013; Wanders et al., 2019). Of note is the push for extended skill at sub‐seasonal time scales (beyond 2 weeks but less than seasonal) (Lang et al., 2020) that has important implications for a range of applications, including disaster risk reduction and for different economic sectors (Morss et al., 2008). Criteria for choosing a set of seasonal climate models are based on their resolution (space and time), availability of hindcasts (historic forecasts) to evaluate their skill, the skill of the models for the particular application, and availability of forecasts operationally.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the temporal correlations of the daily NAO index beyond the synoptic time scale could contribute to exploring the possibilities for subseasonal‐to‐seasonal (S2S) predictions in the North Atlantic area and Europe. There are ongoing international efforts to advance the capability of S2S predictions (Lang et al., 2020; Mariotti et al., 2018, 2020). Present S2S predictions of the NAO are generally not without problems (Albers & Newman, 2021; Smith et al., 2016), most likely related to the signal‐to‐noise paradox (Dunstone et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subseasonal forecasting has long been considered a "predictability desert" due to its complex dependence on both local weather and global climate variables (Vitart et al, 2012). Nevertheless, recent large-scale research efforts have advanced the subseasonal capabilities of operational physics-based models (Vitart et al, 2017;Pegion et al, 2019;Lang et al, 2020), while parallel efforts have demonstrated the value of machine learning and deep learning methods in improving subseasonal forecasting (Li et al, 2016;Cohen et al, 2018;Hwang et al, 2019;Arcomano et al, 2020;He et al, 2020;Yamagami & Matsueda, 2020;Wang et al, 2021;Watson-Parris, 2021;Weyn et al, 2021;Srinivasan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%